2016
DOI: 10.3390/ijms17030380
|View full text |Cite
|
Sign up to set email alerts
|

A RNA-DNA Hybrid Aptamer for Nanoparticle-Based Prostate Tumor Targeted Drug Delivery

Abstract: The side effects of radio- and chemo-therapy pose long-term challenges on a cancer patient’s health. It is, therefore, highly desirable to develop more effective therapies that can specifically target carcinoma cells without damaging normal and healthy cells. Tremendous efforts have been made in the past to develop targeted drug delivery systems for solid cancer treatment. In this study, a new aptamer, A10-3-J1, which recognizes the extracellular domain of the prostate specific membrane antigen (PSMA), was des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Despite the most recent advances, cancer treatments, such as chemotherapy and radiotherapy, still have significant limitations regarding side effects, the major one being, of course, damage to healthy cells. Consequently, cancer treatments with minimal drug and radiation doses have been in the spotlight [ 89 ] due to the fact that they (attempt to) target, specifically, non-healthy cells. Some cell receptors expressed in normal cells are overexpressed in cancer cells; thus, efficiency could be enhanced whilst minimizing the damage to normal cells [ 90 ].…”
Section: Aptamers As Chemotherapy Agentsmentioning
confidence: 99%
“…Despite the most recent advances, cancer treatments, such as chemotherapy and radiotherapy, still have significant limitations regarding side effects, the major one being, of course, damage to healthy cells. Consequently, cancer treatments with minimal drug and radiation doses have been in the spotlight [ 89 ] due to the fact that they (attempt to) target, specifically, non-healthy cells. Some cell receptors expressed in normal cells are overexpressed in cancer cells; thus, efficiency could be enhanced whilst minimizing the damage to normal cells [ 90 ].…”
Section: Aptamers As Chemotherapy Agentsmentioning
confidence: 99%
“…A DNA-RNA hybrid aptamer targeting PSMA was instead used to functionalize, via biotin-streptavidin coupling, SPIONPs loaded with DOX. The resulting SPIO-Apt-Dox was effectively employed as a specific delivery platform for prostate cancer therapy [74]. …”
Section: Aptamer-nanoparticles Systemsmentioning
confidence: 99%
“…Huang et al (2008) demonstrated that ∼80 aptamers could be linked covalently to the surface of Au-Ag nanorods using thiolated functional groups on the aptamers. Recent studies have attested to the therapeutic success of aptamer-nanoparticle conjugates with higher efficiencies (Azhdarzadeh et al 2016;Hong et al 2016;Leach et al 2016;Liu et al 2016). These interesting studies include antiepithelial cell adhesion molecule aptamermediated detection of cancer biomarkers at the level of femtomoles (Hong et al 2016).…”
Section: Aptamer-conjugated Nanoparticlesmentioning
confidence: 99%